The Role of Nutritional Knowledge About Anemia on Adherence to Iron Tablet Consumption in Pregnant Women - Setyaningrum, Risma Ayu; Widiyaningsih, Endang Nur (Prosiding University Research Colloquium, 2023)
Anemia is one of the health problems that is in the spotlight, especially in pregnant women. The incidence of anemia in Indonesia in 2018 reached 48,9%. Anemia in pregnant women can cause miscarriage, low birth weight, prematurity, and even death of mother and baby. One of the factors that can affect pregnancy anemia is adherence to taking iron tablets. The compliance of pregnant women in consuming iron tablets can be influenced by knowledge about anemia, because knowledge will affect the mother’s understanding of the benefits of iron tablets in pregnant women. The study aimed to determine the correlation between knowledge about anemia with compliance consuming iron tablets (Fe) in pregnant women at the Tambora District Health Center. The research was an analytic observasional study with a cross-sectional research design. The sample in this research was 96 third trimester pregnant women selected by consecutive sampling method. Data collection used a knowledge and compliance questionnaire with 25 and 10 question items respectively. Data were analysed using Fisher’s Exact Test. The result also looked at the characteristics of the respondents which showed that most of the respondents, including the age not at risk were 78,1%, the last education of the respondents belonged to the advanced education group of 69,8%, and more than one third of the respondents were not working (78,1%). Good and poor knowledge of pregnant women about anemia has the same percentage, namely 50%. Obedience of pregnant women in consuming iron tablets showed more compliance, namely 79,2%. The result of the analysis with Fisher’s Exact Test showed a significant correlation between knowledge about anemia and adherence to consuming iron tablets with p-value = 0,001. The conclusion obtained is that knowledge of anemia can significantly affect pregnant women’s adherence to taking iron tablets.